Baobab tree (Adansonia digitata L) parts: nutrition, applications in food and uses in ethno-medicine - a review - Bamalli, Zahrau; Mohammed, Abdulkarim Sabo; Mohd Ghazali, Hasanah; Karim, Roselina (Austin Publishers, 2014)
Baobab (Adansonia digitata) is a multi-purpose tree with tender root, tubers, twigs, fruit, seeds, leaves and flowers which are edible. Owing to the nutritional and medicinal benefits of baobab tree parts, it have been used for various purposes for the past two centuries in Africa, and some parts of Asia. This has in recent times led to some statutory bodies approving its use in certain food products. This paper presents a review on the nutritional benefits of the baobab tree parts vis-à-vis its fruit pulp, seeds and leaves. In addition, the medicinal applications of the tree parts as well as the medicinal compounds contained are discussed. This paper finally concludes with the nutritional benefits of the seed oil for possible use as a premium oil.